Advances in the Propolis Chemical Composition between 2013 and 2018: A Review. Issue 1 (14th November 2019) - Šturm, Luka; Ulrih, Nataša Poklar
Abstract : Propolis is a lipophilic sticky substance collected by bees that has been used by humans for centuries. Owing to its healing, antioxidant, and other medicinal properties, its chemical composition has been widely studied. Most pharmacological properties of propolis have been attributed to its phenols and terpenes, mainly flavonoids, phenolic acids, and their derivatives. More than 500 components of propolis were known from different parts of the world until 2012. In this article, 305 new constituents of propolis described between 2013 and 2018 are being reviewed, with 19 additional compounds that were discovered between 2011 and 2012, and were excluded from a similar previous review article. Altogether more than 850 compounds were isolated from propolis until 2018.